Предмет: Алгебра,
автор: Danpel
Уравнение ........................................
только распишите так ,чтобы учитель поверил что это делал я
Приложения:
Ответы
Автор ответа:
0
Решение
Общий знаменатель ( Х + 1 )( Х - 1 ) = х^2 - 1
Х не равен ( - 1 ) ; 1
( Х( Х - 1 ) + х( Х + 1 ) ) / ( х^2 - 1 ) = 2 2/3
( х^2 - х + х^2 + х ) / ( х^2 - 1 ) = 2 2/3
2х^2 / ( х^2 - 1 ) = 8/3
8( х^2 - 1 ) = 3•2х^2
8х^2 - 8 = 6х^2
2х^2 = 8
Х^2 = 4
Х1 = 2
Х2 = - 2
Общий знаменатель ( Х + 1 )( Х - 1 ) = х^2 - 1
Х не равен ( - 1 ) ; 1
( Х( Х - 1 ) + х( Х + 1 ) ) / ( х^2 - 1 ) = 2 2/3
( х^2 - х + х^2 + х ) / ( х^2 - 1 ) = 2 2/3
2х^2 / ( х^2 - 1 ) = 8/3
8( х^2 - 1 ) = 3•2х^2
8х^2 - 8 = 6х^2
2х^2 = 8
Х^2 = 4
Х1 = 2
Х2 = - 2
Похожие вопросы
Предмет: Биология,
автор: nadavasileva302
Предмет: Биология,
автор: prostoakk81
Предмет: Биология,
автор: sadrievnail159
Предмет: Математика,
автор: 3до2
Предмет: Математика,
автор: lengrineva55